2011
DOI: 10.5897/ajb11.124
|View full text |Cite
|
Sign up to set email alerts
|

Changes in endogenous hormone concentrations during inflorescence induction and development in pineapple (Ananas comosus cv. Smooth Cayenne) by ethephon

Abstract: This study investigated the changes of five endogenous hormones in the shoot apex and the white bases of D-leaf during the inflorescence induction and development of 'Smooth Cayenne' pineapple, using 14-month-old pot-grown plants as material and ethephon as flower forcing agent. Results showed that application of ethephon increased the level of endogenous ethylene (C 2 H 4), abscisic acid (ABA) and 2-isopentyl adenine (2-iP) while it decreased the concentration of indole-3-acetic acid (IAA), gibberellic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 7 publications
(10 reference statements)
2
8
0
1
Order By: Relevance
“…TFLs prevent flowers from developing on the inflorescence apex, suppress the FMI genes LFY and AP1 and maintain the inflorescence meristem [44][45]. In the present work, the expression of the pineapple AG and FT genes was induced, and the expression of TFLs was repressed in response to ethephon application at 8 days after ethephon flower induction; the results were in accordance with those of previous physiological research in which, after eight days, ethephon-treated pineapple plants showed signs of inflorescence development and the phyllome stopped developing [15]. Likewise, the fold changes in the expression of the AG, TFL and FT genes were higher in CP than in SC, which probably explained why the effectiveness of ethephon application for floral induction in the pineapple plants categorized as Queen (i.e., CP) was more significant.…”
Section: Degs Associated With Fmi Contributed To the Difference In Thsupporting
confidence: 82%
“…TFLs prevent flowers from developing on the inflorescence apex, suppress the FMI genes LFY and AP1 and maintain the inflorescence meristem [44][45]. In the present work, the expression of the pineapple AG and FT genes was induced, and the expression of TFLs was repressed in response to ethephon application at 8 days after ethephon flower induction; the results were in accordance with those of previous physiological research in which, after eight days, ethephon-treated pineapple plants showed signs of inflorescence development and the phyllome stopped developing [15]. Likewise, the fold changes in the expression of the AG, TFL and FT genes were higher in CP than in SC, which probably explained why the effectiveness of ethephon application for floral induction in the pineapple plants categorized as Queen (i.e., CP) was more significant.…”
Section: Degs Associated With Fmi Contributed To the Difference In Thsupporting
confidence: 82%
“…In this study, a higher concentration of ethephon might be perceived as one type of stress by pineapple seedlings, which resulted in the expression of ethylene receptors being sharply increased after ethephon treatment ( Figure 3 ). On the other hand, our previous study showed that after ethephon application, the liberation of endogenous ethylene in both the shoot apex and D-leaf increased sharply until the 8th day when it reached the peak ( Liu et al, 2011 ); thus, at a higher concentration of endogenous ethylene, more ethylene receptors were bound to ethylene, resulting in a gradual decrease of the transcription of the receptors ( Figure 3 ). The reduction in ethylene receptor levels can increase the sensitization of plants to ethylene; subsequently, a lower concentration of ethylene can stimulate the ethylene response ( Tieman et al, 2000 ; Cancel and Larsen, 2002 ; Wang et al, 2013a ) and induce pineapple flowering.…”
Section: Discussionmentioning
confidence: 85%
“…Di mana yang di maksud dengan wisata di sana bukan hanya mengenai wisata alam, akan tetapi wisata di sana merupakan sebuah konsep yang kemudian berupaya di promosikan oleh pemerintah kota dalam hal bagaimana kerukunan umat antara agama sampai pada perbedaan etnisitas di sana yang kemudian di pelihara secara terus menerus oleh pemerintah kota dan untuk itu pula dalam pengembangan kota cerdas (smart city) di tomohon sekaligus di manfaatkan oleh pemerintah menjadi sebuah ikon dari kota di utara pulau Sulawesi ini (Tomohon, n.d.). Hal tersebut sebenarnya bukan hal baru lagi dalam kenyataan sehari hari di Sulawesi Utara sendiri, di mana kota Manado pun seturut dengan daerah daerah yang lain sebenarnya sudah melakukan hal yang sama dengan kota Tomohon di mana faktor kerukunan itu menjadi ikonik dari kota tersebut (Lukow, 2013). Namun berbeda hal nya dengan kota Tomohon, kota Manado sendiri tidak mencanangkan itu dalam arah pengembangan pemasaran pintar (smart branding) mereka, di mana potensi tersebut memang ada, namun rupa rupanya belum di sadari betul oleh pemerintah kota bahwa sanya hal tersebut bisa di jadikan sebuah branding atau pemasaran kota yang sebenarnya merupakan ikon yang paling mungkin dan paling dekat dengan kultur atau budaya di sana.…”
Section: Metode Penelitianunclassified